Health priorities and perceived health determinants among Western Australians attending the 2011 LGBTI Perth Pride Fairday Festival - Comfort, Judith; McCausland, Kahlia (Australian Health Promotion Association, 2013)
Issue addressed: Although data exist demonstrating poorer health indicators on a range of health outcomes for lesbian, gay, bisexual, transsexual and intersex (LGBTI) people, there is little information as to how this group perceives the relative importance of different health issues or what the underlying reasons behind poorer health may be. Method: A self-completed survey was administered to people attending the October 2011 LGBTI Perth Pride Fairday Festival. Three hundred and fifty-one people completed the survey, resulting in a total of 335 useable surveys. One hundred and seventy-eight participants identified as female, 145 as male, four as transgender and eight as other genders. Results: Depression, anxiety, excessive worry or panic attacks and problems in family relationships were reported as the most important individual health issues, whereas depression, suicide and HIV/AIDS were seen as the most important health issues affecting the LGBTI community. Discrimination was rated the most important social factor impacting on the health and wellbeing of this community. Conclusions: When members of the LGBTI community were asked to rank health issues of importance both individually and as a community, the results indicate that mental health issues are of prime concern. Discrimination and the stress of living as part of this minority group were seen as contributing to this. Health promotion and public health need to be responsive to these issues if real gains are to be made in reducing the health inequities affecting this group. So what?: This research highlights the link between social justice, social inclusion and health outcomes. The health of LGBTI people is rarely considered by mainstream agencies, despite poorer health outcomes. Sensitive and targeted public health interventions that resonate with the community and that acknowledge the impact of being part of this marginalised group are required.